Treatment of HeartMate II Short-to-Shield Patients With an Ungrounded Cable: Indications and Long-Term Outcomes. Issue 4 (April 2020) - Coyle, Laura; Graney, Nicole; Gallagher, Colleen; Paliga, Robin; Yost, Gardner; Pappas, Pat; Macaluso, Gregory; Tatooles, Antone
Abstract : Despite modifications and a procedure to externally replace the distal portion of the percutaneous lead, damage to the wiring insulation causing an electrical short to ground, referred to as a short to shield (STS), has become an important factor in the longevity of the HeartMate II left ventricular assist device (LVAD). Device exchange has been the suggested treatment option. The aim of this study was to evaluate the long-term clinical outcomes of patients with an STS supported on an ungrounded cable. A retrospective review of all patients (n = 479) implanted with a HeartMate II at our center between January 2008 and December 2017 was performed. Patients with a documented STS maintained on an ungrounded cable were examined. Patient characteristics, time from device implantation to STS, treatment strategies, and duration of support on an ungrounded cable were summarized. The association between support with an ungrounded cable and clinical outcomes was evaluated. A total of 53 (11% of 479) patients (83% males and 81% destination therapy) with an STS were supported on an ungrounded cable for a median duration of 195 days (range 2 days to 3.3 years). Patients were more active (New York Heart Association [NYHA] p < 0.001, 6 minute walk test [6MWT] p = 0.003) and had a trend toward increased weight gain ( p = 0.055) from time of implant to STS. Duration of support before the STS was 1.9 years (range 165 days to 8.6 years). Twenty-two patients were treated directly with an ungrounded cable and 31 patients underwent an external driveline repair and still required an ungrounded cable within 2 days (range 0 days to 1.3 years). During the study period, 38 patients were maintained on an ungrounded cable: 21 patients were ongoing for 299 days (range 114 days to 2.8 years), 11 patients transplanted after 79 days (range 7–295 days), four patients died because of comorbid conditions after 1.6 years (range 141 days to 3.2 years), one patient exchanged for thrombosis after 229 days, and one patient explanted after 279 days. The other 15 patients developed a phase-to-phase electrical short after 51 days (range 2 days to 3.3 years): 14 patients underwent a successful pump exchange and one patient transplanted within 2 days. No patients died because of support with an ungrounded cable or worsening lead damage necessitating device exchange. With extended durations of support, some patients with a HeartMate II LVAD will experience device failure in the form of an STS. Select patients with an STS can be safely supported on an ungrounded cable for several years with close monitoring. This treatment approach should be considered before a device exchange.